Unofficial Premium Application Trading a Comparative Analysis between Conventional and Sharia Economics Concepts - Muhammad Sarip; Fatroyah Ars Himsyah (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
In the era of Disruption 5.0, the proliferation of applications has significantly impacted various aspects of community life. This study delves into the realm of buying and selling unofficial premium apps, aiming to analyze the influencing factors and practices from both Islamic and conventional economic perspectives. Adopting a descriptive qualitative approach, the research utilizes a phenomenological method to explore community explanations of the social conditions related to unofficial premium app transactions. Data collection involves library research and online sources, including books, journals, articles, YouTube, Google, and social platforms. The findings reveal that unofficial app transactions often exhibit elements of gharar, leading to user losses. This underscores the importance of transparency and adherence to transactional pillars and conditions to mitigate such losses. The study emphasizes the necessity for a comprehensive exploration of both conventional and Sharia economic concepts in light of current technological developments